Peningkatan Kesadaran Toleransi Melalui Seminar Moderasi Beragama di Desa Batur Utara - Faisal Huda, Ahmad; Mawardi, Imam; Zulkarnen, Ivan (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2024)
Indonesia is a country with an almost unrivaled diversity of tribes, cultures, ethnicities, languages and religions in the world. This diversity is a destiny given by God to be accepted as a gift. In this context, religious moderation emerges as an approach that is considered important to care for the grace that God has given, while facilitating dialogue and cooperation between religious communities. This is the background of the religious moderation seminar in North Batur Village, Kintamani District, Bangli Regency. The participants of this activity were 60 people consisting of students, interfaith youth, and the general public. The hope is to raise awareness about the importance of religious moderation and build cooperation and create an open and sustainable dialog space. The activity was held on Tuesday, July 25, 2023 at the North Batur Village Multipurpose Hall with speakers I Wayan Sudarma, M. Si and Hadi Purwanto, S. Ag. The activity was carried out classically by presenting participants and speakers in the same location, where the speakers delivered the material and then held discussion and question and answer sessions. Overall, this activity provided a new and comprehensive view to all participants who attended the North Batur Village Multipurpose Hall regarding religious moderation